The BEACH Domain Is Critical for Blue Cheese Function in a Spatial and Epistatic Autophagy Hierarchy - Sim, Joan; Osborne, Kathleen A.; Argudo García, Irene; Matysik, Artur S.; Kraut, Rachel (Frontiers in Cell and Developmental Biology, 2019)
Drosophila blue cheese (bchs) encodes a BEACH domain adaptor protein that, like its human homologue ALFY, promotes clearance of aggregated proteins through its interaction with Atg5 and p62. bchs mutations lead to age-dependent accumulation of ubiquitinated inclusions and progressive neurodegeneration in the fly brain, but neither the influence of autophagy on bchs-related degeneration, nor bchs' placement in the autophagic hierarchy have been shown. We present epistatic evidence in a well-defined larval motorneuron paradigm that in bchs mutants, synaptic accumulation of ubiquitinated aggregates and neuronal death can be rescued by pharmacologically amplifying autophagic initiation. Further, pharmacological rescue requires at least one intact BEACH-containing isoform of the two identified in this study. Genetically augmenting a late step in autophagy, however, rescues even a strong mutation which retains only a third, non-BEACH containing isoform. Using living primary larval brain neurons, we elucidate the primary defect in bchs to be an excess of early autophagic compartments and a deficit in mature compartments. Conversely, overexpressing full-length Bchs induces mature compartment proliferation and rescues neuronal death. Surprisingly, only the longest Bchs isoform colocalizes well with autophagosomes, and shuttles between different vesicular locations depending on the type of autophagic impetus applied. Our results are consistent with Bchs promoting autophagic maturation, and the BEACH domain being required for this function.